Origanum Vulgare L. Essential Oil Inhibits Virulence Patterns of Candida Spp. and Potentiates the Effects of Fluconazole and Nystatin in Vitro - Santander-Meyer, R (BioMed Central Ltd, 2022)
Background: Recurrence and resistance of Candida spp. infections is associated with the ability of these microorganisms to present several virulence patterns such as morphogenesis, adhesion, and biofilm formation. In the search for agents with antivirulence activity, essential oils could represent a strategy to act against biofilms and to potentiate antifungal drugs. Objective: To evaluate the antivirulence effect of Origanum vulgare L. essential oil (O-EO) against Candida spp. and to potentiate the effect of fluconazole and nystatin. Methods: The effect of O-EO was evaluated on ATCC reference strains of C. albicans and non-albicans Candida species. Minimum inhibitory concentration (MIC) was determined through broth microdilution assay. Adhesion to microplates was determined by crystal violet (CV) assay. An adapted scratch assay in 24-well was used to determine the effect of essential oil on biofilms proliferation. Viability of biofilms was evaluated by MTT reduction assay and through a checkerboard assay we determined if O-EO could act synergistically with fluconazole and nystatin. Results: MIC for C. albicans ATCC-90029 and ATCC-10231 was 0.01 mg/L and 0.97 mg/L, respectively. For non-albicans Candida strains MIC values were 2.6 mg/L for C. dubliniensis ATCC-CD36 and 5.3 mg/L for C. krusei ATCC-6258. By using these concentrations, O-EO inhibited morphogenesis, adhesion, and proliferation at least by 50% for the strains assayed. In formed biofilms O-EO decreased viability in ATCC 90029 and ATCC 10231 strains (IC50 7.4 and 2.8 mg/L respectively). Finally, we show that O-EO interacted synergistically with fluconazole and nystatin. Conclusions: This study demonstrate that O-EO could be considered to improve the antifungal treatment against Candida spp. © 2022, The Author(s).